A comprehensive review on feasibility of different agro residues for production of bio-oil, bio-char and pyro-gas - Shah, Jinesh B.; Valaki, Janak B. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Burning of post-harvest non-edible agro residues (biomass) are the major source of environmental and soil pollution, affecting the lives of millions of people, especially in certain demography of developing countries like India. Non edible agro residues contain toxic structural constituents, making it unsuitable for cattle feed. However, due to its cellulosic and lignocellulosic constituents, it has the potential to be used as a promising feedstock to develop value added energy products. Authors in this review paper have comprehensively reviewed the technological aspects related to conversion of agro residues into value added energy products like bio-oil, bio-char, and pyro gas. Various non-edible agro residues like Cotton stalk, castor stalk, Maize stalk, Rice straw, Rice husk, Corn cob, Sugarcane bagasse, and wheat straw etc., have been reviewed for its potential as feedstock material for thermo chemical conversion to obtain energy products like bio-oil, bio-char, and pyro-gas. Different physio-chemical properties, its chemical characterization methods, different bio-oil upgradation techniques, Techno-economic analysis (TEA), and Life Cycle Assessment (LCA) have been reviewed for different thermo-chemical conversion processes. The reviewed works reveal that byproducts derived from pyrolysis of non-edible agro residues have potential to be used as biofuels. Bio-oils after upgradation may be used as fuel, bio-char with appropriate pulversing may be used as soil nutrient, and pyro-gas may be used as energy gas or carrier gas for process industries. LCA of different processes for different agro residue-based biofuels indicate that conversion of biomass into energy fuels is an sustainable, and economical solution for the environment point of view and economic point of view through pyrolysis process as compare to the other conversion processes because pyrolysis process can accommodate agro waste and produce bio-char and pyro-gas along with bio-oil having capacity to generate good revenue.